Pengujian Usability Testing Menggunakan Metode System Usability Scale untuk Menilai Aplikasi SIKUU - Nia Saputri Utami; Khansa Salsabila Suhaimi; Tria Kasnalestari; George Ray Banurea; M. Imam Robani; Dani Rahmadana (Sekawan Institut, 2025)
SIKUU or sistem informasi kendali suhu dan lampu is an android based application created with the purpose to monitoring temperature, light density, number of people, and electrical power consumption in a room. SIKUU needs to be tested to determine the level of ease and the purpose of application. Usability testing is the method for testing it. An easy method to use for usability testing is the system usability scale (SUS). SUS Method very popular because of its advantages such as involves end user directly, no special criteria for selecting end user, can be used for fewer respondents but the results are still reliable, the test scale is easy to understand, and the results are effective because it can immediately categorize the application as usable or not. Then, for SIKUU, usability testing was carried out involving 35 respondents from Institute Technology of Sumatera particurally from various study programs. These respondents were introduced to the SIKUU for the first time. The final SUS score is 71,14 which indicates that the acceptability level is in the acceptable category, and adjective rating in the good category. Meanwhile, i terms of the SUS percentile rank, the score falls within category C. In this study, the primary focus of the usability testing was solely on the final score. Therefore, form the users' perspective, SIKUU is considered feasible for use.